CORRELATION OF TNF-Î‘ EXPRESSION TO CLINICAL STADIUM IN NASOPHARYNGEAL CARCINOMA - Susilo, Riko; Farhat; Asnir, Rizalina A; Yudhistira, Ashri; Daulay, Elvita Rahmi; Chrestella, Jessy (INTERNATIONAL JOURNAL OF NASOPHARYNGEAL CARCINOMA (IJNPC), 2020)
Introduction: Nasopharyngeal carcinoma (NPC) is one of the most common malignancies in Indonesia with over 13.000 new cases reported yearly, especially in the male. The TNF-? serum is reported as a new biomarker to predict bone invasion, post-therapy distant metastasis, and poor life sustainability in NPC. Objective: To identify the expression of TNF-? in regards to the clinical stage of NPC. Material and methods: This is an analytic study with 126 NPC samples of patients in Haji Adam Malik General Hospital. Results: NPC mostly found in age group 41-60 years (57.1%), male (71.4%),non-keratinizing SCC (79.4%), and stage IV group (54.8%). In immunohistochemistry evaluation, most of TNF-? overexpressed in non-keratinizing SCC(68.0%), T3-T4 (50.8%), N2-N3 (62.7%) and clinical stage III-IV (69.9%). Spearman's test for categorical correlation yield a p-value of <0,001. Conclusion: There is a significant correlation between TNF-? expression and the stage of NPC.